2013
DOI: 10.2139/ssrn.2338723
|View full text |Cite
|
Sign up to set email alerts
|

Financial Literacy Among Working Young in Urban India

Abstract: The main objective of the Working Paper series of IIMA is to help faculty members, research staff, and doctoral students to speedily share their research findings with professional colleagues and to test out their research findings at the pre-publication stage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 15 publications
0
41
0
4
Order By: Relevance
“…In other words, the above definition focused on three basic dimensions of financial literacy which are financial knowledge, financial behavior and financial attitude. In line with Agarwalla et al (2013) and Potrich et al (2015) this paper adopted the definition proposed by OECD.…”
Section: Financial Literacymentioning
confidence: 99%
See 2 more Smart Citations
“…In other words, the above definition focused on three basic dimensions of financial literacy which are financial knowledge, financial behavior and financial attitude. In line with Agarwalla et al (2013) and Potrich et al (2015) this paper adopted the definition proposed by OECD.…”
Section: Financial Literacymentioning
confidence: 99%
“…According to research, individuals with high financial behavior are more likely to participate in stock market and formal financial markets for investment (Klapper and Panos, 2011;Jennifer and Chi, 2018) pay bills on time, anxiously evaluate financial products, prefer savings than borrowings in crisis time, self-assess the affordability of products (Atkinson and Messy, 2012;Agarwalla et al, 2013) actively save, have a bank account, have a formal credit, more capacity of spending (Klapper and Panos, 2011;Atkinson and Messy, 2012;Agarwalla et al, 2013) prefer low cost borrowing (Allgood and Walstad, 2013;Khalifa, 2018) accumulate and manage assets well (Van Rooij et al, 2007), plan and monitor household budget and personal finance (Atkinson and Messy, 2012;Agarwalla et al, 2013) and do retirement planning (Lusardi and Mitchell, 2008;2011a;Van Rooij et al, 2009). Eniola and Entebang (2016) stated that an entrepreneur with high level of financial literacy perform better towards their business success.…”
Section: Financial Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…A study by Agarwalla et al (2013) considered the influence of various socio-demographic factors on different dimensions of financial literacy among the working young in urban India. The study observed that women have significantly less financial knowledge and showed significantly inferior financial choice behaviour compared to men but they showed significantly superior financial attitude 6 compared to men.…”
Section: Introductionmentioning
confidence: 99%
“…6 This survey measured the financial attitude of the respondents using three items recommended by the OECD to capture the respondent’s extent of belief in planning, propensity to save and propensity to consume (Agarwalla et al, 2013). …”
mentioning
confidence: 99%